Integrasi Gender dalam Perencanaan Pembangunan Desa melalui SDGs Desa di Desa Kemojing, Cilacap - Pambudi, Bagas Satya; Setiadi, Rukuh (Teknik PWK (Perencanaan Wilayah Kota), 2024)
The development model in Indonesia which is centralized and top-down creates many gaps in the achievement of development outcomes, such as the gap between men, women and marginalized groups in gaining access, control, participation, and benefits of development programs/activities, especially in rural in Indonesia. These four aspects need to be implemented in gender responsive planning through policies and programs systematically by placing priority on gender equality, one of which is through the SGDs Desa. This study looks at the level of implementation of gender integration through SDGs Desa in relation to rural development planning in Kemojing Village as a pilot project. The research was conducted with a quantitative approach through data collection techniques in the form of questionnaires up to 90 respondents, interviews, field observations, and document review. The analytical technique used includes 2 technical analysis, checklist analysis and scoring analysis. The checklist produces the level of disclosure while the scoring produces the aspect index value. The results showed that the characteristics of the existing planning in Kemojing Village were 81.67% gender responsive to indicators of aspects of participation, access, benefits, and control. This is supported by the role of the Government in planning an integrated village program, through which village facilitators have succeeded in increasing individual capacity in updating data. Regarding the level of gender integration in the Desa Terpadu Program, the community participation aspect reached 45.19%, the access aspect was 82.59%, the benefit aspect was 70.37%, and the control aspect was 88.52%. The success of implementing gender integration in existing planning and program in Kemojing Village is superior in terms of control and access. This indicates that the closedness of community participation is still a challenge regardless of the participatory approach used in the SDGs Desa. Research findings become input in determining planning policies and efforts to realize gender responsive planning and the sustainability of village development programs.